Quality evaluation and influencing factors analysis of 6-minute walking test in coronary heart disease patients (冠心病患者6分钟步行试验质量评价与原因分析) - WANG Shanshan (王珊珊) (中西医结合护理)
Objective To investigate the influencing factors of accuracy of 6-minute walking test (6MWT) for patients with coronary heart disease, and to summarize strategies to improve the quality of 6MWT. Methods The oxygen uptake and heart rate at anaerobic threshold in the Cardiopulmonary Exercise Test (CPET) were set as the standards of testing, and the peak oxygen uptake and maximal heart rate of 6MWT among different groups were analyzed by chi-square test. The improvement plan was made based on the influencing factors analysis. Results There was a significant difference between oxygen uptake at anaerobic threshold in CPET and peak oxygen uptake in 6MWT(P＜0. 01)among all participants, and there was a significant difference between oxygen uptake at anaerobic threshold in CPET and peak oxygen uptake in 6MWT in participants with symptoms and aged between 50 and 71 years old(P＜0. 01). There was a significant difference between heart rate at anaerobic threshold in CPET and maximal heart rate in 6MWT(P＜0. 01)among all participants, and There was a significant difference between heart rate at anaerobic threshold in CPET and maximal heart rate in 6MWT in participants with symptoms and aged between 50 and 71 years old(P＜0. 01). Conclusion Taking CEPT as an standard, factors influencing the outcomes of 6MWT should be taken into consideration, and improvement measures should be carried out to improve the test accuracy. It is suggested that quality of 6MWT should be strengthened from following aspects: patient health education, kinesiophobia, financial burden, time of conducting 6MWT after PCI and role of cardiac rehabilitation specialist nurses. (目的 研究影响冠心病患者6分钟步行试验(6MWT)评估准确性的原因并分析总结方法, 提高6MWT完成质量。方法 以心肺功能运动试验(CPET)的无氧阈摄氧量与无氧阈心率作为达标标准, 使用卡方检验分析不同分组的6MWT峰值摄氧量与最大心率数据, 探讨测试结果的原因, 并制定改善方案。结果 全体受试者CPET中的无氧阈与6MWT中的峰值摄氧量比较, 差异有统计学意义(P＜0. 01); 不同组别间CPET中的无氧阈与6MWT中的峰值摄氧量比较, 有症状组、老年组差异有统计学意义(P＜0. 01)。全体受试者CPET无氧阈心率与6MWT最大心率比较, 差异有统计学意义(P＜0. 01), 不同组别间CPET中的无氧阈与6MWT中的峰值摄氧量比较, 有症状组、老年组差异有统计学意义(P＜0. 01)。结论 以CEPT作为标准分析影响6MWT结果的原因并提出改善方法, 从而提高6MWT的准确性; 根据结果分析对患者健康教育、运动恐惧、经济负担、PCI术后6MWT评估时间及心脏康复专科护士角色功能几个方面提出改善方法并实施。)